2021
DOI: 10.1002/slct.202102949
|View full text |Cite
|
Sign up to set email alerts
|

β‐Ketoesters: An Overview and It's Applications via Transesterification

Abstract: The transesterification process has attained more significant importance in synthesizing a variety of commercial and noncommercial β-ketoesters using alcohols and variety of acetoacetates. β-Ketoesters have been considered essential synthons in synthetic organic chemistry because of electrophilic and nucleophilic reactive sites and are used as key intermediates in synthesizing the diversity of complex drug molecules. This review provides an overview of the synthesis of β-ketoesters, various reaction mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 226 publications
0
3
0
Order By: Relevance
“…We next turned our attention towards β-ketoesters which are fundamental synthons in organic chemistry. (37)(38)(39) Preliminary experiments starting from commercially available methyl ester 4a(X) using stoichiometric catalyst showed that L-Cys can also facilitate this transformation.…”
Section: Extended Scopementioning
confidence: 99%

Organocatalytic hydration of activated alkynes

González-Rodríguez,
González-Granda,
Lavandera
et al. 2024
Preprint
“…We next turned our attention towards β-ketoesters which are fundamental synthons in organic chemistry. (37)(38)(39) Preliminary experiments starting from commercially available methyl ester 4a(X) using stoichiometric catalyst showed that L-Cys can also facilitate this transformation.…”
Section: Extended Scopementioning
confidence: 99%

Organocatalytic hydration of activated alkynes

González-Rodríguez,
González-Granda,
Lavandera
et al. 2024
Preprint
“…Recently, it has gained more attention in synthesizing drugs, polymers, and biologically active compounds. [75]…”
Section: Transesterificationmentioning
confidence: 99%
“…Several commercial and non‐commercial β‐ketoesters were synthesized through transesterification method utilizing alcohols and variety of acetoacetates. Recently, it has gained more attention in synthesizing drugs, polymers, and biologically active compounds [75] …”
Section: Applications Of Samarium(iii) Triflate In Organic Synthesismentioning
confidence: 99%